2021
DOI: 10.3389/fcell.2021.720288
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Iron and Zinc on Mitochondria: Potential Mechanisms of Glaucomatous Injury

Abstract: Glaucoma is the most substantial cause of irreversible blinding, which is accompanied by progressive retinal ganglion cell damage. Retinal ganglion cells are energy-intensive neurons that connect the brain and retina, and depend on mitochondrial homeostasis to transduce visual information through the brain. As cofactors that regulate many metabolic signals, iron and zinc have attracted increasing attention in studies on neurons and neurodegenerative diseases. Here, we summarize the research connecting iron, zi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 193 publications
(210 reference statements)
1
15
0
Order By: Relevance
“…It is known that both Zn 2+ and mitochondrial dysfunction contribute to progressive RGC loss following optic nerve injury [ 11 ]. The mitochondrial zinc metalloprotease OMA1 senses mitochondrial stress and regulates mitochondrial homeostasis [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that both Zn 2+ and mitochondrial dysfunction contribute to progressive RGC loss following optic nerve injury [ 11 ]. The mitochondrial zinc metalloprotease OMA1 senses mitochondrial stress and regulates mitochondrial homeostasis [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondria are involved in various biological processes, such as energy metabolism, signaling, reactive oxygen species (ROS) production, Ca 2+ regulation, anti-pathogenic mechanisms, and programmed cell death (e.g., apoptosis and ferroptosis) [ 7 , 8 , 9 , 10 ]. Recent evidence has suggested mitochondrial vulnerability, such as NAD + decline, mitochondrial fission increase, and mitochondrial unfolded protein response, as an emerging hypothesis for the pathogenesis of RGC injury [ 11 , 12 ]. Some mitochondria-targeted treatments (e.g., vitamin B3) have been shown to offer RGC protection in animal models and clinical trials [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(71) Moreover, Zn has been reported to inhibit various mitochondrial enzymes, such as mitochondrial complex I, aconitase, cytochrome c oxidase, α-ketoglutarate dehydrogenase, glyceraldehyde-3-phosphate dehydrogenase, and monoamine oxidase. (72) Thus, the energy failure pathway in mitochondria is suggested to be involved in the process of Zn-induced neurotoxicity.…”
Section: Contributions Of Zn To Ischemia-induced Neuronal Death and T...mentioning
confidence: 99%
“…We demonstrated that the admin­istration of sodium pyruvate, an energy substrate, significantly inhibited Zn-induced death in GT1-7 cells.‍ ( 66 ) Sheline et al ‍ ( 70 ) reported that Zn exposure decreased the levels of NAD‍ + and ATP in cultured cortical neurons and that treatment with pyruvate restored the NAD‍ + level. Administration of pyruvate attenuated neuronal death after ischemia also in vivo .‍ ( 71 ) Moreover, Zn has been reported to inhibit various mitochondrial enzymes, such as mitochondrial complex I, aconitase, cytochrome c oxidase, α-ketoglutarate dehydrogenase, glyceraldehyde-3-phosphate dehydrogenase, and monoamine oxidase.‍ ( 72 ) Thus, the energy failure pathway in mitochondria is suggested to be involved in the process of Zn-induced neurotoxicity.…”
Section: Contributions Of Zn To Ischemia-induced Neuronal Death and T...mentioning
confidence: 99%